Combined effectiveness of prior and current season influenza vaccination in northern Spain: 2016/17 mid-season analysis - Castilla, Jesús (Euro Surveill, 2017)
The 2016/17 mid-season vaccine effectiveness estimate against influenza A(H3N2) was 15% (95% confidence interval: −11 to 35) in Navarre. Comparing to individuals unvaccinated in the current and four prior seasons, effectiveness was 24% for current and 3–4 prior doses, 61% for current and 1–2 prior doses, 42% for only current vaccination, and 58% for 3–4 prior doses. This suggests moderate effectiveness for different combinations of vaccination in the current and prior seasons.